Estudo da aprendizagem sobre variabilidade estatística: uma experiência de formação com futuros professores dos anos iniciais da Educação Básica - Silva, Marcílio Farias da (2017)
Future teachers of Statistics in the early years of Basic Education, pursuing a teaching degree in Pedagogy at higher education institution in the state of São Paulo, Brazil, have exhibited difficulties in the conceptual understanding of statistical contents that are crucial to the development of statistical literacy, including difficulties in the perception of variability. The purpose of this investigation was to identify and characterize evidence of statistical knowledge elements that constitute the statistical literacy of future Statistics teachers currently pursuing a degree in Pedagogy in Brazil. Evidence was identified by analyzing concept maps and the resolution of activities during a workshop on statistical variability designed for these students. The theoretical framework for the investigation comprised statistical studies focusing on variability and the construction of statistical literacy. The progress achieved by participating in the workshop was evaluated in terms of levels of literacy (as defined by Iddo Gal), as well as types of mobilization and levels of knowledge functioning (as per Aline Robert) and concept maps (as proposed by Joseph Novak). Twelve students aged 21 to 57 completed the workshop, six of whom were attending the 3rd year of a Pedagogy program (and had already attended a Statistics course) and six the 2nd year (who had not attended the Statistics course). None had previous contact with contents involving dispersion measures, such as amplitude, interquartile range, or mean deviation. The workshop comprised five sessions focusing on basic concepts of Statistics, including classification of variables and concepts of mean, median, mean deviation, amplitude, and quartiles, supplemented with exercises to highlight the various measures of variation and explore the concept of variability using dot plots. Indicators of development of basic notions of statistical content that make up statistical literacy (as per Gal) were identified—namely, variation reasoning combined with the concept of mean and comprehension of statistical terms, particularly mean, quartiles, and deviation, viewed as tools for perceiving data variation and obtaining a result. An element of mathematical knowledge was found to pose an obstacle to the development of statistical literacy (as per Gal): the use of numerical scales in the construction of boxplots. The analysis showed that the level of statistical content knowledge exhibited by these future teachers is currently in development and has not attained the cultural level of statistical literacy (as defined by Gal), despite evidence of experience with elements pertaining to statistical knowledge